Jawabanmu

Jawaban paling cerdas!
2014-06-05T00:19:56+07:00
X + y = 8 ⇔ x = 8 - y atau y = 8 - x
a. Untuk x = 8-y maka zx - y = 1 ⇔ z(8-y) - y = 1
                                                    ⇔ 8z - yz - y = 1
                                                    ⇔ y(-z-1) = 1 - 8z
                                                     ⇔ y = 1 - 8z    atau y = 8z - 1
                                                               -z - 1                    z + 1
b. Untuk y = 8 - x maka zx - y = 1 ⇔ zx - (8-x) = 1
                                                      ⇔ zx - 8 + x = 1
                                                      ⇔ zx + x = 9
                                                      ⇔ x(z+1) = 9
                                                               x     =     9     
                                                                          z + 1
2 5 2
2014-06-05T05:51:52+07:00
X + y = 8 ⇔ x = 8 - y atau y = 8 - x

                           ⇔ y = 1 - 8z    atau y = 8z - 1
                                     -z - 1                    z + 1

                                  x     =     9     
                                              z + 1